The influence of catur guru on a person's intentions: a literature review from an economic perspective - Wijaya, Bagus Kusuma; Permana, I Putu Hendika (Global Researcher Network, 2025)
This study aims to explore the influence of Catur Guru a central ethical and spiritual concept in Balinese Hindu tradition on individual economic intentions. Catur Guru comprises four respected figures: Guru Swadyaya (God), Guru Wisesa (government), Guru Pengajian (teachers/lecturers), and Guru Rupaka (parents). Using an exploratory qualitative literature review approach, this research examines how values passed down by each of these